Algorithm for operating an ordinary engineering system as a quantum bit. Issue 1 (31st December 2022) - Itami, Teturo; Matsui, Nobuyuki; Isokawa, Teijiro; Kouda, Noriaki; Hashimoto, Takanori
Abstract : We show an algorithm for the previously proposed quantum computer using classical apparatuses. The target system is not limited to mass points but is a general engineering system that has a more manageable form in equipping terminal edge. After we define such system as "ordinary engineering system, " the method of quantum mechanical optimum feedback control of the nonlinear system is applied. The method makes an ordinary engineering system into a quantum one. As an example that is as stale as possible, a temperature control system is taken. Simulation studies show that our system works as a 1- q u b i t quantum computer without the special large-scale peripheral equipment required to maintain quantumness. The proposed system is a classic system that is everywhere, so it is easy for anyone to understand. Another advantage is that easy-to-use one-dimensional system can be applied.